Desempenho de novilhos Nelore confinados alimentados com óleo de linhaça in natura ou protegido - Carvalho, Victor Galli [UNESP] (2014)
The objective was to evaluate the performance, carcass characteristics, body growth, measurements of body and ultrasonic of 35 Nellore steers, with 18 month-old, and 397.74 ± 14.07 kg of body weight fed with 60% concentrated and corn silage and with protected linseed oil (PLO) of rumen degradation during 35, 70 or 105 days before slaughter, with oil in natura during 105 days or with no oil (73% of TDN and 2.9% of EE). The diets with oil were isoenergetic (76% of TDN and 3.1% of EE), whereas the addition of in natura and protected oil was 3.4 and 4.5% of DM, respectively. The experimental design was a randomized block, and the results were evaluated by mixed model and treatments were compared by non orthogonal contrasts. The measures were correlated with carcass traits by Pearson’s analysis. There was no difference between treatments for feed efficiency (0.132 kg DM intake/kg weight gain), daily weight gain (1.24 kg), final body weight (522.71 ± 27.99 kg), yields of carcass (57%) and total meat cuts (68.7%). The addition of linseed oil in the diet increased (P<0.05) the ether extract intake, weights of kidney-pelvic-inguinal fat, hump, top sirloin butt + bottom sirloin butt, inner skirt steak cuts and fat trimmings; the yield of hump, top sirloin butt + bottom sirloin butt and fat trimmings; and decreased daily growth and final width of chest, compared with treatment without oil. Compared to in natura linseed oil, the PLO provided during the 105 days of feedlot caused (P<0.05) lower ether extract intake and an increase in eye of round yield, daily growth and final chest girth. The increasing durations of PLO supplementation increased (P<0.05) ether extract intake; altered the weights of the kidneys, kidney-pelvic-inguinal fat, fat trimmings and bones in the carcass; the yields of eye of round and bones; and the final pelvic contour of animals. With the exception of width of chest, all body ...